THE ROLE OF EDUCATIONAL INSTITUTIONS AND FAMILY ENVIRONMENT IN TEACHING MOTHER LANGUAGE READING LITERACY IN PRIMARY GRADES - Abdufattoyeva Gulazzam Kabiljan girl (Zeta Repository, 2023)
In this article, the tasks of educational institutions and the family environment for the good organization of mother tongue reading literacy in primary grades and their role in improving students' knowledge are discussed.